Long-Term Safety and Effectiveness of Dimethyl Fumarate in Patients with Multiple Sclerosis Treated in Routine Medical Practice: Final Analysis of the ESTEEM Study - Krupa Shah Pandey; Kathryn Giles; Konstantin Balashov; Richard Macdonell; Jörg Windsheimer; Mikel Martinez; Ivan Božin; Stephanie Raynaud; Matthew Scaramozza; Oksana Mokliatchouk; Zhaonan Sun; Nicholas Belviso; et al. (Neurology and Therapy)
Abstract Introduction Dimethyl fumarate (DMF) has demonstrated a favorable benefit–risk profile in patients with relapsing–remitting multiple sclerosis (RRMS) in clinical and real-world studies. The ESTEEM study (NCT02047097) was conducted to assess the long-term safety and effectiveness of delayed-release DMF in patients with relapsing forms of MS in routine clinical practice. We report final outcomes from ESTEEM with up to 6.5 years of follow-up. Methods Patients newly prescribed DMF were recruited from 393 sites globally. The primary objective was to assess the incidence and type of serious adverse events (SAEs) and adverse events (AEs) leading to discontinuation of DMF. Secondary objectives included assessment of DMF effectiveness on annualized relapse rate (ARR) and patient-reported outcomes (PROs). Results Overall, 5124 patients received ≥ 1 dose of DMF. The mean (standard deviation [SD]) age at enrollment was 40.0 (11.2) years; 74% of patients were female. Patients received DMF for a mean (SD) duration of 31.0 (22.7) months. Primary reasons for discontinuation were AEs (n = 1237; 24%); the most common were gastrointestinal AEs (n = 469; 9%), blood and lymphatic disorders (n = 218; 4%), and vascular disorders (n = 200; 4%). SAEs occurred in 391 (8%) patients, most commonly infections and infestations (n = 102; 2%). Adjusted ARR declined by 90% (95% confidence interval [CI]: 90–91%; p < 0.0001), from 0.81 (95% CI 0.79–0.84) 12 months before enrollment to 0.08 (95% CI 0.08–0.09) 6 years after enrollment. The estimated proportion of patients free from confirmed disability progression sustained over 48 weeks was 87.0% at month 60. Mean scores for physical and psychological impact, fatigue, health, and productivity remained stable over 5 years. Conclusion DMF demonstrated a safety profile in real-world clinical practice consistent with the known profile of DMF. Relapse rates were low and both ARR and PROs remained stable over time. Trial Registration ClinicalTrials.gov Identifier NCT02047097.